Physical examination tests of the shoulder: a systematic review with meta-analysis of individual tests - Hegedus, E. J.; Goode, A.; Campbell, S.; Morin, A.; Tamaddoni, M.; Moorman, C. T.; Cook, C. (British Journal of Sports Medicine, 2008)
Objective: To compile and critique research on the diagnostic accuracy of individual orthopaedic physical examination tests in a manner that would allow clinicians to judge whether these tests are valuable to their practice.